Romania in International Relations 1944-1947. The State of Law versus the State of Facts - Stefan, Gheorghe (Journal of Danubian Studies and Research, 2023)
The process of establishing communism in Romania was not a singular phenomenon, on the contrary, it was multiplied on the scale of Central and South-Eastern European integrity, within a vast scenario of "finlandization" of the area by the Soviets with the tacit consent of its allies. Direct and brutal involvement in domestic politics, the imposition of "friendly governments" is by definition a violation of the constitutional principles of sovereignty, invalidating from the outset the regimes of "popular democracy". The phenomenon will be presented at that time and later throughout the communist regime, as a natural evolution of society, a struggle between old and new ad The phenomenon will be presented at that time and later throughout the communist regime, as a natural evolution of society, a struggle between the old and the new, the truth being largely distorted.